Implication of sperm chromosomal abnormalities in recurrent abortion and multiple implantation failure. Issue 4 (October 2015) - Caseiro, Ana Lara; Regalo, Ana; Pereira, Elisa; Esteves, Telma; Fernandes, Fernando; Carvalho, Joaquim
Abstract Currently, some infertility treatment centres provide sperm karyotype analysis, although the impact of sperm chromosomal abnormalities on fertility is not yet fully understood. Several studies using fluorescence in-situ hybridization (FISH) to analyse sperm chromosomal constitution discovered that the incidence of aneuploidy is increased in individuals with a history of repeated abortion or implantation failure and is even higher in cases of oligoasthenoteratozoospermia (OAT), abnormal somatic karyotype or in spermatozoa retrieved directly from the testis or epididymis, showing that the application of FISH in these cases may be of some benefit for improving the reproductive outcome. This article presents the results of clinical trials of FISH analysis on spermatozoa, the medical indications for performing this examination, its results in infertile patients and the advantages when performing genetic counselling prior to treatment. Also discussed is the possibility of applying the latest techniques of genetic analysis in these cases and the potential benefits for improving the prognosis of male infertility.